A Supplementary Protein Food for Pregnant Women with Chronic Energy Deficiency to Improve Fetal Growth - Prameswari, Fajria Saliha Puspita; Marliyati, Sri Anna; Dewi, Mira (Jurnal Gizi dan Pangan, 2020)
The aimed to analyze the effect of protein-sourced supplementary foods for pregnant women with CED to improve fetal growth. The pre-post study test involved 44 pregnant women with a Mid Upper Arm Circumference (MUAC) of <23.5cm in Bogor City, West Java. The subjects were divided into two groups, first was the PG group, consist of pregnant women who received the protein-sourced supplementary foods. The second was the PCG group where the pregnant women recieved the standard government supplementary food (GSF) for eight weeks. Data regarding the fetal growth was obtained using USG, the inidactor measured were the femur length and estimated fetal weight. The increase of femur length and estimated fetal weight were used as the fetal growth parameters. Analysis of Covariance was applied to obtain the effect of intervention by controlling other covariate variables. The result showed that the improvement of estimated fetal weight (EFW) and femur length (FL) in both groups were similar (p>0.05). Despite the fact that the PG group showed lower compliance compared to the PCG (p>0.05). The findings suggest that our protein-sourced supplementary foods had a similar effect with the GSF on fetal growth of pregnant women with CED.